Robotska celica za spajanje požarnih loput - Jevšnik, Jaka (Ventil (Ljubljana), 2007)
This article presents a robot cell for the assembly of fire dampers that are designed to prevent fire and smoke propagation in fire ducts. The aim of this new cell is the automation of the process and the implementation of a new joining method. Spot welding has been replaced by joining with cold-forming. The cell consists of an ABB IRB6600 robot with the IRC5 controller and a special, custom-made gripper, pallet system with a cold-forming joining system, two presses and a rotating table. The application is quite complex with a virtually unlimited number of different sizes of dampers possible.
Keywords: hladno spajanje; požarne lopute; robotska celica